Integrating Escape Rooms and E-Learning Technologies for Smart Cities Development: A Simulation Study - Tawafak, Ragad M.; Mathew, Roy; Alfarsi, Ghaliya; Alsideiri, Abir; Malik, Sohail Iqbal (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The paper gives an intensive review of the current state of escape rooms and e-learning innovations within smart city instruction. It consolidates existing information, making it available to teachers, analysts, and policymakers. The paper bridges two distinct but complementary areas by combining insights from escape rooms and e-learning innovations. The paper distinguishes holes within the current investigation and hones, indicating ranges requiring assist examination. It also highlights openings for future advancement and development within the utilization of escape rooms and e-learning advances. This study examines 13 review papers related to each innovation. The strategy proposes a system that gives commonsense rules and contemplations for teachers and engineers. The paper outlines how escape rooms and e-learning advances have been effectively coordinated and utilized in keen city instruction in Oman. The paper finds and examines the potential effect of escape rooms and e-learning advances on learning results, emphasizing their part in improving engagement, inspiration, and critical thinking abilities among learners. The study reveals the center on innovative educational innovations; the paper contributes to forming more intelligent and feasible urban situations.